Kajian Kekhususan Inang Stegobium paniceum (Coleoptera: Anobiidae) - F. X. Wagiman; V. Poerdriesti (Jurnal Perlindungan Tanaman Indonesia, 1998)
The study of the host range of Stegobium paniceum (L.) (Coleoptera: Anobiidae) was conducted at the Laboratory of Research center for Biological Control (RCBC), Gadjah Mada University, under room temperature of 26.55±0.72oC–30.66±0.40oC and 57.38±5.53% relative humidity. The materials tested were seventh materials of stored products in their original and flour form. No Choice Method and Free Choice Method were to determine the applied host range and host specificity. New generation of S. paniceum produced from a material was used to indicate that the material was its host. The results showed that the main host of S. paniceum was coriander, and its alternative hosts were caraway seed, rice, dry ginger, candlenut, and nutmeg, while S. paniceum could not survive on pepper. The material form did not significantly affect the S. paniceum development.